Women Teacher's Barrier in Professional Development: A Narrative Inquiry - Bhatta, Devi (Tejganga Darpan, 2024)
This qualitative study explores the experiences of women teachers in the Kailali district of one ward in Nepal, who face barriers in professional development. This study had a small sample size, with two participants from both private and public schools, each with over ten years of teaching experience. I employed a critical theory approach and conducted semi-structured interviews via the Zoom app to collect the data. The findings revealed that women teachers are not prioritised in training and workshops which creates a barrier in professional development. Additionally, the dual burden of home and work responsibilities stifled their creativity and impacted their financial situation. The study suggests that the policy for recruiting women teachers should be inclusive. Further research is needed to investigate the issue of barriers in the overall development of women teachers, both at home and in the workplace, to support their professional development and growth.